Dynamically tunable high‐efficiency broadband terahertz linear polarization converter based on Dirac semimetal metamaterials. Issue 8 (8th January 2020) - Meng, Wanli; Hou, Baoyu; Cao, Qiuhong; Lin, Hongmei; Zhou, Wei; Li, Zhaoxin; Li, Dehua
Abstract: An electrically‐tunable polarization converter with a dynamic range of 2.026 to 2.481 THz is designed and simulated in this work. A dumbbell‐like Dirac semimetal metamaterial is fabricated and attached to a Teflon plate, with a perfect electric conductor as the substrate. Simulation results show that for a 22‐μm‐thick Teflon plate and a Fermi level is 60 meV, the polarization conversion rate reaches 100% at the two resonance frequencies of 2.072 and 2.428 THz. Moreover, the polarization conversion rate exceeds 85% in the frequency range of 2.026 to 2.481 THz.